GRAMMATICAL NUMBER CATEGORY IN THE NOUN PHRASE IN ENGLISH AND UZBEK (Neo Scientific Peer Reviewed Journal, 2025)
This article reveals the similarities and differences between the forms of numbers in English and Uzbek. The grammatical structure and explanations of both languages are presented. While English has complex rules for expressing numbers, Uzbek offers a simpler and simpler way of expressing them. This comparative analysis will help teachers and language learners to understand the content of number concepts more deeply, and will clarify the relationship between artistic language and culture.